Global Halal Supply Chains : Challenges and Strategies for Sustainable Trade - Askarova, Anel; Shymanska, Kateryna; Brellíková, Miriam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the global Halal supply chains, focusing on their challenges and opportunities in achieving sustainable trade. As the Halal market rapidly expands beyond food into sectors like pharmaceuticals and logistics, the study analyzes cultural, economic, and regulatory factors shaping its development. Using trade data, SWOT analysis, and expert interviews, the research proposes strategies to enhance certification, logistics, and international cooperation in the Halal industry.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses